IMPACT OF THREE DIFFERENT DOUBLE BAFFLE DESIGNS ON THE THERMAL PERFORMANCE OF SQUARE DUCTS - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2022)
CFD analyses of flow characteristics and heat transfer topology in a heat exchanger duct (HXD) placed with three various configurations of the double V-baffles (DVB) are reported. Parameters of interest are DVB height ratios (b/H = 0.05 – 0.25), gap spacing ratios (g = 0.05 – 0.40), flow directions (+x,-x), and DVB configurations (Type I, II and III). Laminar flow with Reynolds numbers (based on the inlet conditions) between 100 – 2000 is measured. The present problem is solved with the finite volume method (a commercial program). Fluid flow and heat transfer characteristics in the tested duct are described. Thermal assessments of the tested duct are also presented. Simulation results showed that the installation of the DVB in the HXD results in higher heat transfer rate due to the creation of the vortex flow and the disturbance of the thermal boundary layer (TBL). Different flow structures and heat transfer behavior are observed when gap spacing ratios, flow directions and DVB shapes are changed. In addition, the type II DVB provides the highest TEF of 3.55 at b/H = 0.10, g/H = 0.25 for the-x flow direction.
Keywords: double V-baffles; flow structures; heat exchanger; heat transfer; thermal performance